A biochemical study of the development of woolliness in nectarines (Prunus Persica Nectarina CVS Flavortop and Fantasia) - Hartmann, P. E. O.(Phillip Eric Otto) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1987.